2013
DOI: 10.21083/ajote.v3i2.2060
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Conflicts and Moral Dilemmas Experienced by Physical Education Teachers in Tanzania

Abstract: The purpose of this study was to explore the ethical conflicts and moral dilemmas (ECMD) experienced by Physical Education (PE) teachers. The study also sought to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Consequently, we cannot cross compare the existing findings with similar literature in ELT. Probably, there is only one study by Mabagala (2013) in Physical Education context, also mentioned above, which did not find significant variations in the conflicts teachers of various genders reported.…”
Section: Importance Of Teachers' Gender For Teachers' Pattern Oo Moramentioning
confidence: 88%
See 1 more Smart Citation
“…Consequently, we cannot cross compare the existing findings with similar literature in ELT. Probably, there is only one study by Mabagala (2013) in Physical Education context, also mentioned above, which did not find significant variations in the conflicts teachers of various genders reported.…”
Section: Importance Of Teachers' Gender For Teachers' Pattern Oo Moramentioning
confidence: 88%
“…Since we did not find other studies comparing moral dilemmas experienced and inexperienced ELT teachers' encounter in their practice, cross comparison of the current findings with those of the literature is not feasible. To our knowledge, the only available studies investigating the types of moral conflicts faced by teachers of various years of experience are Koc and Buzzelli (2016) and Mabagala (2013) who probed into early childhood education and Physical Education contexts respectively. Neither of the studies found significant differences in the nature of moral dilemmas of novice and experienced teachers.…”
Section: Importance Of Teaching Experience For Teachers' Pattern Of Mmentioning
confidence: 99%
“…Professionalism increases a person's importance by improving his technical skills. These efficiencies of teachers not only bring out the God-given potential of students and help them achieve their educational goals but also fulfill their dreams of a bright and successful future (Mabagala, 2018). Teaching professionals work on many research projects to improve their teaching skills.…”
Section: Introductionmentioning
confidence: 99%